Imprinting disorders in children born after ART: a Nordic study from the CoNARTaS group. Issue 5 (12th May 2020) - Henningsen, A A; Gissler, M; Rasmussen, S; Opdahl, S; Wennerholm, U B; Spangmose, A L; Tiitinen, A; Bergh, C; Romundstad, L B; Laivuori, H; Forman, J L; Pinborg, A; et al.
Abstract: STUDY QUESTION: Is the risk of imprinting disorders increased in children conceived after SUMMARY ANSWER: We found an adjusted odds ratio (AOR) of 2.84 [95% CI: 1.34–6.01] for Beckwith–Wiedemann syndrome in ART children, while the risk of Prader–Willi syndrome, Silver–Russell syndrome or Angelman syndrome was not increased in children conceived after ART. WHAT IS KNOWN ALREADY: Earlier studies, most of them small, have suggested an association between ART and imprinting disorders. STUDY DESIGN, SIZE, DURATION: This was a binational register-based cohort study. All children conceived by ART in Denmark ( n  = 45 393, born between 1994 and 2014) and in Finland ( n  = 29 244, born between 1990 and 2014) were identified. The full background populations born during the same time periods in the two countries were included as controls. Odds ratios of imprinting disorders in ART children compared with naturally conceived (NC) children were calculated. The median follow-up time was 8 years and 9 months for ART children and 11 years and 9 months for NC children. PARTICIPANTS/MATERIALS, SETTING, METHODS: From the national health registries in Denmark and Finland, we identified all children diagnosed with Prader–Willi syndrome ( n  = 143), Silver–Russell syndrome ( n  = 69), Beckwith–Wiedemann syndrome ( n  = 105) and Angelman syndrome ( n  = 72) born between 1994/1990 and 2014, respectively. MAIN RESULTS AND THE ROLE OF CHANCE: We identified a total of 388 children diagnosed with imprinting disorders; 16 of these were conceived after ART. The overall AOR for the four imprinting disorders in ART children compared with NC children was 1.35 [95% CI: 0.80–2.29], but since eight ART children were diagnosed with Beckwith–Wiedemann syndrome, the AOR for this specific imprinting disorder was 2.84 [95% CI: 1.34–6.01]. The absolute risk of Beckwith–Wiedemann syndrome in children conceived after ART was still low: 10.7 out of 100 000 newborns. The risks of Prader–Willi syndrome, Silver–Russell syndrome and Angelman syndrome were not increased in children conceived after ART. LIMITATIONS, REASONS FOR CAUTION: Imprinting disorders are rare events and our results are based on few ART children with imprinting disorders. The aetiology is complex and only partly clarified, and the clinical diagnoses are challenged by a broad phenotypic spectrum. WIDER IMPLICATIONS OF THE FINDINGS: In the existing studies, results on the risk of imprinting disorders in children conceived after ART are ambiguous. This study adds that the risk of imprinting disorders in ART children is very small and perhaps restricted to Beckwith–Wiedemann syndrome. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the Nordic Trial Alliance: a pilot project jointly funded by the Nordic Council of Ministers and NordForsk (grant number: 71450), the Nordic Federation of Obstetrics and Gynecology (grant numbers: NF13041, NF15058, NF16026 and NF17043) and the Interreg Öresund-Kattegat-Skagerak European Regional Development Fund (ReproUnion project). The authors have no conflicts of interest related to this work. TRIAL REGISTRATION NUMBER: N/A